Językowy obraz historii Polski w skeczach współczesnych kabaretów - Adamczyk, Marzena (Acta Universitatis Lodziensis. Folia Linguistica, 2012)
This work addresses the problem of cabaret groups and sketches. First of all, it describes and analyses the linguistic picture of the Polish history, including Polish stereotypes (e.g. the stereotype of a German or Russian person), in sketches of modern cabaret groups. This article presents the linguistic methods of creating a comic interpretation of history used by the authors of sketches. As a result of data analysis, three kinds of sketches are distinguished: historical ones, sketches based on convention, and manners sketches.